Tinjauan Tata Letak Ruang Guna Kelancaran Proses Pelayanan Rekam Medis di UKRM BLUD RSU Banjarbaru Tahun 2014 - Aris Antoni; M. Mun'im Hendrawi; Ulfah Sukmasari; STIKES Husada Borneo (HB PRESS, 2015)
Work space in medical record BLUD RSU Banjarbaru for laying facilities or infrastructure not compliant because of limited moving space. In the medical records BLUD RSU Banjarbaru there are facilities or infrastructure that is not needed advice. And inpatient medical records in place and organized floor space unit medical record. The aim of this study is to minimize the workspace in the work unit medical record BLUD RSU Banjarbaru. This study used a discriptive methot. The research instrument used interview and check list. The technique of collecting through observation and interview. Way of presenting data in the form of text and images. The results of this research work is the layout of the unit medical record BLUD RSU Banjarbaru which consists of a registration, managers & staff room, and storage space is not in accordance with the existing theory, so it makes employees less comfortable in the work. In the medical record the workspace is divided into two rooms the work room and a registration with a different layout, so that affects the medical record service. Spatial workspace medical records BLUD RSU Banjarbaru consisting of registration space, space managers and staff have not been in accordance with the sequence of work, especially in the area managers and staff. Thus affecting the officers in their duties and will affect the medical record service. Design workspace medical records BLUD RSU Banjarbaru especially in space managers and staff for the placement of infrastructure less in accordance with the existing theory. Thus affecting the medical record service.